2010
DOI: 10.1097/mpa.0b013e3181dbf647
|View full text |Cite
|
Sign up to set email alerts
|

α-Smooth Muscle Actin Expressing Stroma Promotes an Aggressive Tumor Biology in Pancreatic Ductal Adenocarcinoma

Abstract: OBJECTIVES: Pancreatic ductal adenocarcinoma (PDAC) is often characterized by a prominent desmoplastic stroma that is induced partially by alpha-smooth muscle actin (SMA)-expressing activated pancreatic stellate cells (PSCs). This study aimed to investigate the significance of alpha-SMA expression in PDAC and the correlation between alpha-SMA mRNA levels and the patient prognosis. METHODS: We obtained formalin-fixed, paraffin-embedded tissue samples from 109 patients with PDAC, who underwent pancreatectomy at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 49 publications
6
77
2
1
Order By: Relevance
“…However, the combined pericyte signature at the mRNA level was much more effective at predicting relapse (P ¼ 0.00067) than the level of aSMA staining (P ¼ 0.03691). High aSMA protein has also been reported to be of prognostic value in colorectal cancer (7) and at the mRNA level in pancreatic adenocarcinoma (8,46). In contrast, recent studies in murine models of pancreatic adenocarcinoma provide evidence in favor of aSMA þ cells having a role in limiting tumor growth and metastasis by either suppressing immune surveillance (47) or perhaps decreasing tumor angiogenesis (48).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the combined pericyte signature at the mRNA level was much more effective at predicting relapse (P ¼ 0.00067) than the level of aSMA staining (P ¼ 0.03691). High aSMA protein has also been reported to be of prognostic value in colorectal cancer (7) and at the mRNA level in pancreatic adenocarcinoma (8,46). In contrast, recent studies in murine models of pancreatic adenocarcinoma provide evidence in favor of aSMA þ cells having a role in limiting tumor growth and metastasis by either suppressing immune surveillance (47) or perhaps decreasing tumor angiogenesis (48).…”
Section: Discussionmentioning
confidence: 87%
“…Stromal signatures strongly predict relapse in ovarian, colorectal, pancreatic, and breast cancers (5)(6)(7)(8)(9), contributing to the prevailing view that the TME is pro-tumorigenic. Although sufficient evidence exists to support the notion that recruitment of a cooperative stroma is essential for malignant progression, it is equally plausible that the influx of some stromal elements is the body's attempt to limit cancer spread through fibroblastic encapsulation typical of many tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] In addition, the detection of pancreatic stellate cells immediately adjacent to pancreatic ductal adenocarcinoma epithelium correlates with adverse clinicopathological parameters. 6,7,37 Our group and others have shown that highly contractile pancreatic stellate cells can produce aligned collagen matrices in vitro, and the resultant topography can facilitate pancreatic ductal adenocarcinoma cancer cell migration. [38][39][40] Our immunohistochemical analysis suggests a positive correlation between alpha-smooth muscle actin expression and aligned collagen in the pancreatic ductal adenocarcinoma periductal stroma, which should be further validated on a larger patient cohort for potential mechanistic insight (Figure 4, Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…S1 E and F). The presence of fibrotic foci is a hallmark of pancreatic cancer, and high levels of smooth muscle actin were recently correlated with poor survival of patients with advanced pancreatic ductal adenocarcinomas (17). Pdx1 was also reexpressed in both adenocarcinomas and metastases ( Fig.…”
mentioning
confidence: 99%